AVR System Improvement: Fast and Optimal Tuning PID Control Using Safe Experimentation Dynamics Algorithm - Suid, Mohd Helmi; Ahmad, Mohd Ashraf; Ahmad, Salmiah; Jusof, Mohd Falfazli Mat; Tumari, Zaidi Mohd (International Conference on System Science and Engineering (Online), 2024)
The Automatic Voltage Regulator (AVR) plays a critical role in maintaining the voltage level of a synchronous generator. To enhance its dynamical response, various control strategies have been introduced, with the Proportional-Integral-Derivative (PID) controller being one of the most widely used. However, despite its relatively high dynamic response, there remains room for improvement to achieve more precise and accelerated responses. This paper presents the design of a novel based PID controller for the AVR system, aimed at achieving faster settling to rated voltage and enhancing control accuracy. The parameters of the PID controller are optimized using a single agent self-tuning heuristic optimization method i.e., Safe Experimentation Dynamics Algorithm (SED). This approach aims to improve the dynamic response, particularly in reducing steady-state errors and overshoot. Simulation results, validated using a time-response specifications index, demonstrate the effectiveness of the proposed metaheuristic-based PID controller. Compared to modern metaheuristic optimization- based PID controllers, the proposed method significantly enhances the transient response of the AVR system, showcasing its efficacy and potential for practical implementation.